Morocco : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper quantifies the effect of gender inequality in Morocco on growth, compared with groups of faster growing countries. The results highlight the effect of closing the overall gender gap, which would help narrow up to 1 percentage point the difference between Morocco's GDP per capita and that of benchmark countries in other regions. Simulations also show that gradually closing gender gaps in the labor force participation rate could lead to significant income gains over the long term. Policy recommendations to promote gender equality include investing in secondary education for women and in infrastructure and reforming tax policies and laws that discriminate against women.